The use of vacuum-assisted closure in Fournier’s gangrene - Özlü, Özer; Başaran, Abdulkadir; Kurt, Feyzi (The European Research Journal, 2021)
Objectives: Fournier’s gangrene is an emergency surgical disease which develops and progresses rapidly and there is high risk of mortality with a delay in diagnosis and treatment. The objective of this study is to investigate the impact of vacuum-assisted closure on the clinical outcome in the treatment of Fournier’s gangrene. Methods: A total of 28 patients diagnosed as Fournier’s gangrene and admitted to our hospital from January 2010 to December 2018 are included in this retrospective study. The diagnosis was established on the basis of physical examination. Epidemiological data including gender, age, and presence of diabetes mellitus, clinical outcomes including use of vacuum-assisted closure, length of admittance, the number of debridement and other surgical procedures were evaluated retrospectively from the medical records and the hospital treatment registry. Results: There were 16 (57.1%) male and 12 (42.9%) female patients and the mean age of the patients was 59.54 ± 16.76 years. The mean number of debridement was 3.67 ± 1.5 times and the total hospital stay was 26.67 ± 7.7 days for vacuum-assisted closure group (n = 9). The average number of debridement was 4.11 ± 0.94 times and the total hospital stay was 31.58 ± 6.33 days for the rest of the patients (n = 19). Conclusions: The average number of debridement and hospital stay were lower in patients treated with vacuum-assisted closure. We also observed an increase in patient comfort and the workload of the stuff is decreased as there was less exudate in the vacuum-assisted closure group.